Unlocking the Path to International Expansion: Investigating the Impact of Managerial International Experience on SME Internationalization - Fernando, Ph.D., Agus (President University, 2023)
This study explores the influence of a manager's international experience on small and medium-sized enterprises' (SMEs) internationalization. Contrary to common beliefs, we challenge the notion that international experience is the primary driver of firm internationalization. Using a research model and empirical data from SME managers, we find that a manager's aggressiveness in international markets plays a pivotal role in determining the degree of internationalization achieved by their SME. Aggressiveness in seeking opportunities emerged as a crucial factor for successful internationalization. Additionally, the manager's perception of risk associated with international expansion significantly impacts their level of aggressiveness. Managers with lower risk perceptions are more inclined to pursue international opportunities assertively. On the other hand, a manager's international experience directly affects their ability to recognize opportunities and develop confidence in international markets, driving aggressive behaviors. These findings challenge conventional assumptions and emphasize the importance of a proactive approach to international expansion. The study contributes to a deeper understanding of the complex relationship between a manager's international experience, aggressiveness, and SME internationalization. We encourage future research to further investigate the multifaceted process of international entrepreneurship, offering new perspectives to enhance SME success in global markets.